Pulsed-field gel electrophoresis and ribotype profiles of clinical and environmental Vibrio vulnificus isolates. - Tamplin, M L (1996)
Vibrio vulnificus belongs to the autochthonous bacterial flora of warm estuarine waters. It can cause life-threatening extraintestinal disease in persons who have underlying illness and who consume raw shellfish or contact wounds with estuarine water. Currently, very little is known about genetic diversity within this species. In this report, we describe high-level variation in restriction fragment length polymorphism profiles among 53 clinical and 78 environmental isolates, as determined by pulsed-field gel electrophoresis. In contrast, ribotype profiles showed greater similarity. When combined ribotype profiles of clinical and environmental isolates were analyzed, four predominant clusters were observed. Interestingly, a low number (16%) of clinical isolates were found in cluster C, compared with clusters A, B, and D (range, 50 to 83%). In addition, 83% of all Hawaiian isolates were located in a single cluster, indicating a possible relationship between geography and genotype. We also report that spontaneous translucent colonial morphotypes were distinct by both restriction fragment length polymorphism and biochemical profiles, compared with opaque parent strains.